2002
DOI: 10.1086/339722
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an Extremely Red Object in the Field of HD 155826

Abstract: We have discovered an extremely red object, LSF 1, located 7 00 southwest (P.A. 217) of the bright spectroscopic binary system HD 155826. Originally reported by IRAS as one source detected at 12-60 lm, and found as a single 6-25 lm source of similar flux in the Midcourse Space Experiment Galactic plane survey, two bright point sources were found in arcsecond resolution infrared images obtained with the MIRLIN camera at the Infrared Telescope Facility and confirmed by the Long Wavelength Spectrometer camera on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Contamination by background sources is a significant problem, and follow‐up observations are important to confirm that the IRAS associations are real. Certainly, not all IRAS associations are real, as demonstrated by observations of 55 Cnc (Jayawardhana et al 2002) and HD 155826 (Lisse et al 2002). SCUBA is a useful tool for confirming associations because it gives source positions which are significantly more accurate than those from IRAS .…”
Section: Resultsmentioning
confidence: 99%
“…Contamination by background sources is a significant problem, and follow‐up observations are important to confirm that the IRAS associations are real. Certainly, not all IRAS associations are real, as demonstrated by observations of 55 Cnc (Jayawardhana et al 2002) and HD 155826 (Lisse et al 2002). SCUBA is a useful tool for confirming associations because it gives source positions which are significantly more accurate than those from IRAS .…”
Section: Resultsmentioning
confidence: 99%
“…All concluded that only 2 ± 2% of these stars have hot dust with infrared luminosities f = L ir /L ⋆ > 10 −4 , finding a total of 3 candidates. Other hot dust candidates exist in the literature, however some IRAS excess fluxes have turned out to arise from chance alignments with background objects (e.g., Lisse et al 2002), including the candidate HD128400 from the hot dust survey of Gaidos (1999) (Zuckerman, priv. comm.).…”
Section: Application To Rare Systems With Hot Dustmentioning
confidence: 99%
“…In this study HD 53246 and HD 128400 are in and near the galactic plane respectively, and have been found to have been erroneously identified as hosts of debris. HD 155826, identified by Lisse et al (2002) as being a bogus disk due to source confusion also lies in the galactic plane at b = −0.1. Removal of bogus disks is important when attempting to perform a statistical analysis on disk populations.…”
Section: Background Exclusion and The Importance Of Confirmationmentioning
confidence: 99%